Multiply each equation by a constant that would help to eliminate the y terms. 2x-5y = -21 3x-3y = -18 What are the result

Question

Multiply each equation by a constant that would help to eliminate the y terms.
2x-5y = -21
3x-3y = -18
What are the resulting equations?
6x-15y = -63
– 15x+15y = 90
6x-15y = 63
-15x+15y = 90
6x-15y=-63
– 15x+ 15y = -90

in progress 0
Diễm Thu 6 months 2021-07-23T05:29:27+00:00 1 Answers 10 views 0

Answers ( )

    0
    2021-07-23T05:31:24+00:00

    6x-15y=-63
    -15x+15y=90

    This is because you are multiplying the first equation by a constant of 3 and the second equation by 5 so that you can have -15y and +15y which will cancel each other out.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )